The Use of TPRC and PLAN Strategies in Improving EFL Learners’ Reading Comprehension - Cherly Widya Nofitson; Dian Seviatika Utami (English Instruction, 2020)
The main objective of this study was to compare the ability of EFL learners to understand texts by using Think, Predict, Read, and Connect (TPRC) strategy and Predict, Locate, Add, and Note (PLAN) strategy. The research was a comparative experimental with quantitative method. The subject of the research was the students majoring in Accounting Level I at Language Development Center of UIN Suska Riau in the academic year of 2016/2017. The object of the research was the comparison of students' ability to understand English texts using TPRC strategy and PLAN strategy. Cluster sampling technique was employed to determine the sample of the study. Two classes consisting of 50 students were taken as the sample which was divided into experimental group 1 and the experimental group 2. A pre-test and a post-test were given to both the experimental group 1 and the experimental group 2. Independent t-test and paired sample t-test were used to analyze the data. The results showed that there was a significant difference of the value of students' reading post-test between the experimental group 1 taught using TPRC and experimental group 2 taught using PLAN. The result of T-test was 2.91, df 48, the SD of the experimental group 1 was 10.57 and the experimental group 2 was 7.88. It was discovered that p = 0.005, two tailed value of less than 0.05 (p <0.05). Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. It was also proven that TPRC reading strategy contributed to the enhancement of students' reading comprehension by 32% and PLAN contributed as much as 58%. Therefore, it could be concluded that PLAN strategy gave better results than TPRC strategy